The Palgrave Encyclopedia of Victorian Women's Writing - Scholl, Lesa,Morris, Emily (Springer International Publishing, 2022)
1. Reform – 2. Novels – 3. Health/Wellness – 4. Religion – 5. Economics – 6. Journalism – 7. New Woman – 8. Travel Writing – 9. Poetry – 10. Literary Criticism – 11. Domestic Management – 12. Food Studies – 13. Short Stories – 14. Sexuality – 15. Philosophy – 16. Science – 17. Life Writing – 17. Fashion – 18. Children's Writing – 19. Commonwealth – 20. Art History/Art Criticism – 21. Theatre/Playwrights – 22. Education – 23. Translators – 24. Music – 25. Suffrage – 26. Engineering – 27. Lesbian/Queer Writers – 28. Anthropology/Archaeology – 29. History. Since the late twentieth century, there has been a strategic campaign to recover the impact of Victorian women writers in the field of English literature. However, with the increased understanding of the importance of interdisciplinarity in the twenty-first century, there is a need to extend this campaign beyond literary studies in order to recognise the role of women writers across the nineteenth century, a time that was intrinsically interdisciplinary in approach to scholarly writing and public intellectual engagement. .
10.1007/978-3-030-78318-1
Keywords: Literature; Modern—19th century.; Literature—History and criticism.; History; Modern.